Policing politics : security intelligence and the liberal democratic state - Gill, Peter, 1947- (London ; Portland, Or. : F. Cass, 1994)
Disturbing allegations of abuse of power have been made against the domestic security intelligence agencies in the UK - police special branches and M15. These include improper surveillance, campaigns of disinformation, even the elimination of people believed to be engaged in political violence. Drawing upon extensive foreign material and making use of the social science concepts of information, power and law, this book develops a framework for the comparative analysis of security intelligence which is then applied to the UK agencies. This discussion includes the ambiguous nature of their mandate regarding 'national security'; the ways in which the agencies penetrate society and gather information; the extent to which they are controlled by ministers; and how their activities might be overseen by outside political bodies, and by citizens in general. The book concludes that a thorough investigation is needed into the allegations that have been made, together with proposals for a more democratic system.
What do we know and how do we know it?; the state and security intelligence -- concepts and models; defining the security intelligence mandate; penetration I -- gathering information; penetration II -- producing intelligence; autonomy I -- organization and control of security intelligence agencies; autonomy II -- principles and institutions of oversight; autonomy III -- overseeing the executive; the future of security intelligence. Appendix: Defence Press and Broadcasting Committee D-Notice No. 6.
Includes bibliographical references and index.
Keywords: Intelligence service -- Great Britain; Secret service -- Great Britain; Intelligence operations; Imperial Security Intelligence Service